Health beliefs and prescription medication compliance among diagnosed hypertension clinic attenders in a rural South African hospital - K. Peltzer (AOSIS, 2004)
This study examines the relationship between health beliefs and the use of both prescribed medication and alternative healing agents among at least one year diagnosed hypertensives attending an hypertension out-patient clinic in a rural South African hospital. The sample included 33 men and 67 women, in the age range of 31 to 81 years, (M=60.7 years, SD=9.8 years). Main outcome measures included causative beliefs, health beliefs, and quality of the health care provider patient interaction. From the 100 patients studied 35% were not compliant with prescription medication. Most patients (almost 80%) had taken something else for their high blood pressure apart from prescription medication, especially those who had been non-compliant with prescription medication. Most popular were the use of home remedies and faith healing, followed by traditional healing and over-the-counter drugs. Non-compliant behaviour was associated with the use of alternative healing agents, the belief of curability of hypertension by traditional and faith healers, perceived benefits and barriers of antihypertensive medication and some items of the quality of the practitioner-patient relationship such as not explaining medical problems. Results are discussed in view of improving culturally sensitive compliance behaviour among hypertensive patients.